Honour as emblem: A strategic vision of values in the Guardia Civil - Martínez Viqueira, Eduardo Isidro (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2024)
The initial deployment of the Civil Guards commenced in the autumn of 1844, with their specific regulations being augmented the following year by the renowned Cartilla, an ethical code that anchored the Institute’s value system in ethical honour. The rigorous adherence to these regulations, coupled with a commanding style that was fitting, swiftly propelled the Guardia Civil to high service efficiency and a leading position in Spain’s public security. This foundational ethical framework fostered a genuine institutional culture within the Guardia Civil, reinforcing a true esprit de corps. Presently, the Guardia Civil is dedicated to implementing a new code of conduct that preserves its military essence, drawing upon the enduring values and principles that have historically shaped its ethical path. Consequently, it is imperative to examine the relevance of these historical values in contemporary times. It raises pertinent inquiries: What does honour signify for the Guardia Civil today? Is honour still a valuable concept in the present day? If so, what are the metrics for it? Additionally, the origin of the nickname ’Benemérita’ and its connection to honour warrants exploration. It is evident that a strong correlation exists at the strategic level between the culture of an organization and the ethos of the Civil Guards, both historically and presently. Honour consistently emerges as a fundamental element in this context.